DNA barcoding of Austrian terrestrial isopods (Crustacea: Isopoda: Oniscidea) reveals potential cryptic diversity - Anna-Chiara Barta; Luise Kruckenhauser; Hedda Büttner; Matthäus Greilhuber; Klaus Hasenhütl; Stephan Koblmüller; Lukas Kremp; Oliver Macek; Hanna Sommer; Nikolaus U. Szucsich; Martin Schwentner (PLoS ONE, 2026)
Terrestrial isopods or Oniscidea are a diverse and ecologically important taxon. Austria has a relatively high species diversity with over 60 known species. In this study, we aim to provide DNA barcode reference data for the Austrian Oniscidea and to update the species inventory, which was last reviewed nearly 50 years ago. Although the focus was on freshly collected specimens, we also successfully sequenced historic museum specimens, thereby testing different museomic techniques including Sanger-based and Illumina-based methods. In total, 533 COI barcodes were generated, representing 49 of the 64 species and subspecies reported from Austria (= 76% of the species diversity), including two species not previously reported: Philoscia muscorum muscorum and P. affinis affinis . Several species exhibited large intraspecific genetic distances and the best-scoring ASAP partition (with a threshold of 6.2%) split the 49 studied species into 59 mOTUs. Even the more conservative partition with a threshold of 9.8% suggested the presence of further hitherto unrecognized species. One example is Ligidium germanicum , where we were able to demonstrate minor but consistent morphological differences in the shape of the endopod of pleopod II. COI data of historic specimens was successfully obtained. Sanger-based approaches using mini-barcodes in combination with a prior DNA repair step were more cost and labor effective than Illumina-based genome skimming approaches. This COI barcoding data plays an important role in bridging gaps in the representation of rare soil species, thus supporting the Austrian Barcode of Life Initiative (ABOL) and providing important reference data for future biodiversity and monitoring studies.